Modified transjugular approach for percutaneous atrial septal defect closure - Rishi Ashokkumar Bhargava; Ankur Phatarpekar; Charan P Lanjewar; Prafulla G Kerkar (Wolters Kluwer Medknow Publications, 2017)
Femoral venous route is routinely used for percutaneous closure of atrial septal defects (ASDs). However, a situation may arise where transfemoral approach is not feasible. We describe a successful transjugular closure of a moderate-sized ASD in a 49-year-old symptomatic man with interrupted inferior vena cava, using a novel deployment technique, which helped in overcoming difficulties such as maintaining stable sheath position and minimizing risk of air embolism.